Method for producing hollow microparticles and hollow microparticles

By polymerizing a solution containing fluorinated monomers and a phase separation promoter dispersed in water, the problem of manufacturing large-diameter hollow fluorinated resin particles in existing technologies has been solved. This enables the manufacture of lightweight hollow particles with low refractive index, which are suitable for electronic materials and low refractive index lens materials.

CN115803350BActive Publication Date: 2025-02-25DAIKIN INDUSTRIES LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180047365.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-09
Filing Date
2021-07-07
Publication Date
2025-02-25
Estimated Expiration
2041-07-07

AI Technical Summary

Technical Problem

Existing technologies make it difficult to manufacture hollow fluorinated resin particles with large average particle size, and inorganic particles are heavy, which cannot meet the requirements for lightweight and low refractive index.

Method used

The polymerization process involves dispersing a solution of fluorinated monomers, phase separation promoters, and non-polymerizable solvents in water to form hollow microparticles of fluorinated resin. The process conditions are optimized to increase the average particle size.

Benefits of technology

Hollow microparticles with large average particle size and containing fluorinated resin were successfully manufactured, which are suitable for electronic materials and low refractive index lens materials, reducing dielectric constant and refractive index, and improving the material's lightweight and low dielectric properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115803350B_ABST
    Figure CN115803350B_ABST
Patent Text Reader

Abstract

A production method is provided, which can produce hollow microparticles containing fluorine-containing resin and having a large average particle size. A production method for hollow microparticles, characterized in that it includes the following steps: a dispersion step of dispersing a solution containing a fluorine-containing monomer, a phase separation promoter and a non-polymerizable solvent in water to obtain a dispersion; and a polymerization step of polymerizing the fluorine-containing monomer to obtain hollow microparticles containing fluorine-containing resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing hollow fine particles and the hollow fine particles. Background Art

[0002] Hollow particles with spaces inside the particles are excellent in light weight, low refractive index, low dielectric properties, etc., and various studies have been conducted on them. As such hollow particles, inorganic particles have been used in the past, but the weight of inorganic particles is heavy, so the hollow particles obtained by polymers have been used to replace the research of inorganic particles.

[0003] For example, Patent Document 1 describes hollow resin fine particles containing a resin having fluorine atoms, characterized in that the particles have an average particle size of 10 to 200 nm, a porosity of 10% or more, and a refractive index of 1.30 or less.

[0004] Patent Document 2 describes a method for producing microparticles containing a target component, characterized in that a mixture containing the target component, a specific monomer component, a specific auxiliary polymer and an initiator is dispersed in an aqueous solution of a dispersion stabilizer to perform suspension polymerization.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-213366

[0008] Patent Document 2: Japanese Patent Application Publication No. 2003-96108 Summary of the invention

[0009] Problems to be solved by the invention

[0010] The present invention provides a production method capable of producing hollow fine particles containing a fluorine-containing resin and having a large average particle size. In addition, the present invention provides hollow fine particles containing a fluorine-containing resin and having a large average particle size.

[0011] Means for solving problems

[0012] The present invention relates to a method for producing hollow microparticles, characterized in that it comprises the following steps: a dispersion step of dispersing a solution containing a fluorine-containing monomer, a phase separation promoter and a non-polymerizable solvent in water to obtain a dispersion; and a polymerization step of polymerizing the fluorine-containing monomer to obtain hollow microparticles containing a fluorine-containing resin.

[0013] The fluorine-containing monomer is preferably the following general formula (B 1 ) shown in the monomer (B 1 ).

[0014] CX1 X 2 =CY 1 Z(B 1 )

[0015] (Where X 1 , X 2 and Y 1 are independently H, CH3, F or Cl. Z is F, -Q-Rf 1 -Y(Q is a single bond, -O-, -O-(C=O)- or -C(=O)-O-. Rf 1 It is a fluorinated alkylene group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms. Y is a group represented by F, H, -OH, -COOH, -COOR (R is an alkyl group having 1 to 20 carbon atoms), or the following formula:

[0016] [Chemistry 1]

[0017]

[0018] (Where X 6 ~X 10 are independently a hydrogen atom, a fluorine atom, or a hydrocarbon group having 1 to 8 carbon atoms which may be substituted with fluorine or chlorine) or -SO3H. 1 , X 2 , Y 1 and Z contain one or more F. )

[0019] In addition, the fluorine-containing monomer is more preferably the following general formula (C 1 ):

[0020] CH2=CX 3 -COORf 2 (C 1 )

[0021] (Where X 3 Rf is H, CH3, F, Cl or CF3. 2 It is a fluorinated alkyl group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms. 1 ).

[0022] The phase separation promoter is dissolved in the non-polymerizable solvent at room temperature, and the Sp value of the phase separation promoter is SA (J / cm 3 ) 1 / 2 , the Sp value of the non-polymerizable solvent is set to SB (J / cm 3 ) 1 / 2 It is preferred that the following relationship is satisfied.

[0023] │SA-SB│<3(J / cm 3 ) 1 / 2

[0024] In addition, the phase separation promoter preferably comprises a compound based on the following general formula:

[0025] CH2=CX 4 Y 2

[0026] (Where X 4 Y is H, CH3, F, Cl or CF3. 2 Cl, C6H4R 1 、C6H3R 2 R 3 、COOR 4 or OCOR 5 (Here, R 1 , R 2 , R 3 , R 4 and R 5 The polymer of the polymerized units of the monomer represented by ) is more preferably at least one selected from the group consisting of aromatic vinyl polymers and polyalkyl (meth)acrylates.

[0027] The fluorine content of the fluorine-containing monomer is preferably 30% by mass or more.

[0028] The solution preferably further contains a cross-linkable monomer.

[0029] The non-polymerizable solvent is preferably an aromatic hydrocarbon, an ester, or a saturated hydrocarbon having 8 to 18 carbon atoms, or a halogen-substituted product thereof.

[0030] The above-mentioned dispersing step is preferably the following step:

[0031] A step of dispersing the solution in water at a temperature of 50° C. or higher to obtain a dispersion; or

[0032] A step of dispersing the solution in water at a temperature lower than 50° C. to obtain a dispersion, and heating the obtained dispersion to a temperature of 50° C. or higher.

[0033] Furthermore, the production method of the present invention preferably further comprises a step of adding an oil-soluble initiator to the dispersion after the dispersion step and before the polymerization step.

[0034] Preferably, the method comprises the step of removing the non-polymerizable solvent from the hollow fine particles obtained in the polymerization step.

[0035] The average particle size of the hollow fine particles is preferably 1.0 μm or more.

[0036] The present invention also relates to hollow fine particles characterized in that the hollow fine particles contain a fluorine-containing resin D comprising polymerized units based on a fluorine-containing monomer, wherein the average particle size of the hollow fine particles is 1.0 μm or more.

[0037] The fluorine-containing monomer is preferably the following general formula (B 2 ) shown in the monomer (B 2 ).

[0038] CX 1 X 2 =CY 1 Z(B 2 )

[0039] (Where X 1 , X 2 and Y 1 are independently the same or different and are H, CH3, F or Cl. Z is F, -Q-Rf 1 -Y(Q is a single bond, -O-, -O-(C=O)- or -C(=O)-O-. Rf 1 It is a fluorinated alkylene group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms. Y is a group represented by F, H, -OH, -COOH, -COOR (R is an alkyl group having 1 to 20 carbon atoms), or the following formula:

[0040] [Chemistry 2]

[0041]

[0042] (Where X 6 ~X 10 are independently a hydrogen atom, a fluorine atom, or a hydrocarbon group having 1 to 8 carbon atoms which may be substituted with fluorine or chlorine) or -SO3H. 1 , X 2 , Y 1 and Z contain one or more F. )

[0043] In addition, the above-mentioned fluorine-containing monomer is preferably the following general formula (C 2 ):

[0044] CH2=CX 3 -COORf 2 (C 2 )

[0045] (Where X 3 Rf is H, CH3, F, Cl or CF3. 2It is a fluorinated alkyl group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms. 2 ).

[0046] The hollow fine particles preferably further contain a phase separation promoter.

[0047] The phase separation promoter preferably comprises a compound based on the following general formula:

[0048] CH2=CX 4 Y 2

[0049] (Where X 4 Y is H, CH3, F, Cl or CF3. 2 Cl, C6H4R 1 、C6H3R 2 R 3 、COOR 4 or OCOR 5 (Here, R 1 , R 2 , R 3 , R 4 and R 5 Each of the monomers is independently H, OH or an alkyl group having 1 to 40 carbon atoms which may be substituted with a halogen atom. The polymer of the polymerization unit of the monomer represented by ) is preferably at least one selected from the group consisting of an aromatic vinyl polymer and a polyalkyl (meth)acrylate.

[0050] The fluorine-containing resin D preferably further contains a polymerized unit based on a cross-linkable monomer.

[0051] Furthermore, the fluorine content of the fluorine-containing resin D is preferably 15% by mass or more.

[0052] The hollow fine particles of the present invention preferably consist of a shell composed of the fluorine-containing resin D and a hollow portion and have a single-hole structure.

[0053] Furthermore, the present invention also relates to a curable composition comprising the above-mentioned hollow fine particles.

[0054] In addition, the present invention also relates to a coating composition comprising the above hollow fine particles.

[0055] The hollow fine particles of the present invention are preferably hollow fine particles for electronic materials.

[0056] Effects of the Invention

[0057] The method for producing hollow fine particles of the present invention can produce hollow fine particles containing a fluorine-containing resin and having a large average particle size. In addition, the hollow fine particles of the present invention have a large average particle size despite containing a fluorine-containing resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 middle, Figure 1 (a) is an optical microscope photograph of the suspended droplet before polymerization in Example 1, Figure 1 (b) is an optical microscope photograph of the hollow fine particles after polymerization.

[0059] Figure 2 This is a SEM photograph of the hollow fine particles after polymerization in Example 1.

[0060] Figure 3 middle, Figure 3 (a) is an optical microscope photograph of the suspended droplets before polymerization in Example 2, Figure 3 (b) is an optical microscope photograph of the polymerized microparticles.

[0061] Figure 4 middle, Figure 4 (a) is an optical microscope photograph of the suspended droplet before polymerization in Comparative Example 2, Figure 4 (b) is an optical microscope photograph of the polymerized microparticles.

[0062] Figure 5 middle, Figure 5 (a) is an optical microscope photograph of the suspended droplets before polymerization in Example 4, Figure 5 (b) is an optical microscope photograph of the hollow fine particles after polymerization.

[0063] Figure 6 middle, Figure 6 (a) is a SEM photograph of the particles obtained in Example 4, Figure 6 (b) is the EDX mapping of the shell wall. Figure 6 (c) is a SEM photograph of crushed particles.

[0064] Figure 7 middle, Figure 7 (a) is an optical microscope photograph of the suspended droplets before polymerization in Example 5.

[0065] Figure 8 middle, Figure 8 (a) is an optical microscope photograph of the hollow fine particles after polymerization in Example 5, Figure 8 (b) is a SEM image of the hollow particles after polymerization.

[0066] Fig. 9 This is an example of a cross-sectional SEM photograph of the film 2 produced in the film production 1.

[0067] Fig.10 This is an example of a cross-sectional SEM photograph of the film 2 produced in the film production 1.

[0068] Fig.11This is a graph in which the amount of fine particles added is plotted on the horizontal axis and the dielectric loss tangent is plotted on the vertical axis for the films produced in Examples. DETAILED DESCRIPTION

[0069] The present invention relates to a method for producing hollow microparticles, characterized in that it comprises the following steps: a dispersion step of dispersing a solution containing a fluorine-containing monomer, a phase separation promoter and a non-polymerizable solvent in water to obtain a dispersion; and a polymerization step of polymerizing the fluorine-containing monomer to obtain hollow microparticles containing a fluorine-containing resin.

[0070] The present inventors have conducted research and found that when a fluorinated monomer is polymerized to obtain hollow microparticles containing a fluorinated resin, it is difficult to obtain hollow microparticles with a large average particle size using existing methods. The present inventors have found that even hollow microparticles containing a fluorinated resin can have an increased average particle size by dispersing a solution containing a fluorinated monomer, a phase separation promoter, and a non-polymerizable solvent in water and then polymerizing the solution, thereby completing the method for producing hollow microparticles of the present invention.

[0071] The above-mentioned dispersion step is a step of dispersing a solution containing a fluorinated monomer, a phase separation promoter and a non-polymerizable solvent in water to obtain a dispersion. By dispersing the above-mentioned solution to form droplets, the fluorinated monomer can be polymerized in the droplets. At this time, the phase separation promoter is used to promote phase separation, and even in the case of containing a fluorinated resin, hollow particles with a large average particle size can be obtained.

[0072] Examples of the fluorine-containing monomer include fluorine-containing acrylic monomers, fluorine-containing styrene monomers, and fluorine-containing olefins, but are not particularly limited thereto. Preferred fluorine-containing monomers are, for example, those of the following general formula (B 1 ) shown in the monomer (B 1 ).

[0073] CX 1 X 2 =CY 1 Z(B 1 )

[0074] (Where X 1 , X 2 and Y 1 are independently H, CH3, F or Cl. Z is F, -Q-Rf 1 -Y(Q is a single bond, -O-, -O-(C=O)- or -C(=O)-O-. Rf 1 It is a fluorinated alkylene group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms. Y is a group represented by F, H, -OH, -COOH, -COOR (R is an alkyl group having 1 to 20 carbon atoms), or the following formula:

[0075] [Chemistry 3]

[0076]

[0077] (Where X 6 ~X 10 are independently a hydrogen atom, a fluorine atom, or a hydrocarbon group having 1 to 8 carbon atoms which may be substituted with fluorine or chlorine) or -SO3H. 1 , X 2 , Y 1 and Z contain one or more F. )

[0078] From the perspective of aggregation, the above X 1 and X 2 are independently preferably H, CH3 or F, X 1 and X 2 More preferably, they are both F or H, and even more preferably, they are both H.

[0079] From the perspective of polymerizability and heat resistance of the polymer, the above Y 1 It is preferably H, CH3 or F, more preferably CH3 or F, and further preferably CH3.

[0080] The above Z is preferably F, -Q-Rf 1 -Y, or the following formula:

[0081] [Chemistry 4]

[0082]

[0083] The groups shown.

[0084] From the perspective of polymerizability, the general formula (B 1 ) is more preferably -Q-Rf 1 A group represented by -Y (Q is a single bond, -O-, -O-(C=O)- or -C(=O)-O-).

[0085] From the viewpoint of ease of monomer synthesis, Q is preferably a single bond, -O-(C=O)- or -C(=O)-O-, more preferably -O-(C=O)- or -C(=O)-O-, and further preferably -C(=O)-O-.

[0086] From the perspective of the heat resistance and electrical properties of the polymer, the above Rf 1 The number of carbon atoms in is preferably 1 to 10, more preferably 1 to 6, and even more preferably 1 to 4. 1 Preferably, it is a fluorinated alkylene group that does not contain an ether bond between carbon atoms, and more preferably -CH2-Rf 3 -X 5 (Rf 3 It is a linear or branched fluorine-containing alkylene group having 1 to 19 carbon atoms.5 is H or F. ) represented by the group, the above Rf 3 The number of carbon atoms in the moiety is preferably 1-9, more preferably 1-5, particularly preferably 1-3.

[0087] From the viewpoint of electrical characteristics, Y is preferably F, H or -COOR (R is an alkyl group having 1 to 20 carbon atoms), more preferably H or F, and even more preferably F.

[0088] The above X 6 ~X 10 The hydrocarbon group in is preferably a non-fluorinated alkyl group or a fluorinated alkyl group. The hydrocarbon group preferably has 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms.

[0089] The fluorinated olefin is preferably at least one selected from the group consisting of fluorinated olefins (1) having a functional group, fluorinated olefins (2) not having a functional group, and cyclic fluorinated olefins (3).

[0090] (1) Fluorinated olefins with functional groups

[0091] As the fluorinated olefin (1) having a functional group, the following formula (3) is preferred:

[0092] [Chemistry 5]

[0093]

[0094] (Where X 11 , X 12 and X 13 Same or different, H or F; X 14 is H, F, CF3; h is an integer from 0 to 2; i is 0 or 1; Rf 4 is a fluorinated alkylene group having 1 to 40 carbon atoms or a fluorinated alkylene group having 2 to 100 carbon atoms and having an ether bond; Z 1 A monomer represented by a functional group selected from the group consisting of -OH, CH2OH, -COOH, carboxylic acid derivatives, -SO3H, sulfonic acid derivatives, epoxy groups and cyano groups, wherein CH2=CFCF2ORf is more preferred 4 -Z 1 (Where Rf 4 and Z 1 More specifically, preferably,

[0095] [Chemistry 6]

[0096]

[0097] (Where Z 1 Same as above) and other monomers.

[0098] In addition, as the fluorine-containing olefin (1) having a functional group, CF2=CFORf can also be preferably exemplified. 4 -Z 1 (Where Rf 4 and Z 1 The same as above) monomers, more specifically, include

[0099] [Chemistry 7]

[0100]

[0101] (Where Z 1 Same as above) and other monomers.

[0102] In addition, examples of the fluorinated olefin (1) having a functional group include

[0103] [Chemistry 8]

[0104] CF2=CFCF2-O-Rf 4 -Z 1 CF2=CF-Rf 4 -Z 1 ,

[0105] CH2=CH-Rf 4 -Z 1 、CH2=CHO-Rf 4 -Z 1

[0106] (Where Rf 4 and Z 1 Same as above), etc. More specifically,

[0107] [Chemistry 9]

[0108]

[0109] (Where Z 1 Same as above) etc. However, since the monomers having -OH group, -COOH group and -SO3H group may reduce the electrical properties, it is preferable to use the monomers in an amount within a range that does not reduce the electrical properties.

[0110] As the fluorinated olefin (1) having a functional group, CH2=CF-CF2-O-(CF(CF3)-CF2) is preferred. n -CF(CF3)CH2OH (in the formula, n=0~9), CH2=CF-CF2-O-(CF(CF3)-CF2) n -CF(CF3)COOH (in the formula, n=0~9), CH2=CF-CF2-O-(CF(CF3)-CF2)n -CF(CF3)CN (where n=0-9) or CF2=CF-O-(CF2CF(CF3)O) n -(CF2) m -Z 3 (Where Z 3 is COOH, SO3H or CN, m=1-6, n=0-6. ).

[0111] (2) Fluorinated olefins without functional groups

[0112] From the viewpoint of further improving the electrical properties, the fluorinated olefin (2) having no functional group is preferred. In addition, the mechanical properties, glass transition temperature, etc. of the polymer can be adjusted by selecting the monomer, which is also preferred.

[0113] As the above-mentioned fluorine-containing olefin (2) not containing a functional group, the formula (4) is preferred:

[0114] [Chemistry 10]

[0115]

[0116] (Where X 15 , X 16 and X 18 Same or different, H or F; X 17 is H, F or CF3; h1, i1 and j are 0 or 1; Z 2 is H, F or Cl; Rf 5 It is a substance represented by a fluorinated alkylene group having 1 to 20 carbon atoms or a fluorinated alkylene group having 2 to 100 carbon atoms and containing an ether bond).

[0117] As a specific example, preferably CH2=CH-(CF2) n F(n=1~10), CH2=CF-CF2-O-(CF(CF3)-CF2) n -CF(CF3)H(n=0~9),

[0118] [Chemistry 11]

[0119] Etc. monomers.

[0120] Among them, CF2=CF2 and CF2=CF-O-(CF2) are preferred. n F(n=1~5), CH2=CF-CF2-O-(CF(CF3)-CF2) n -CF(CF3)H(n=0~5), CH2=CH-(CF2) nF (n=1~6), CF2=CF-CF3, CF2=CFCl or CF2=CH2.

[0121] (3) Cyclic fluorinated olefins

[0122] Cyclic fluorinated olefins (3) are preferred from the viewpoints of further improving electrical properties, obtaining fluorinated hollow fine particles with a higher glass transition temperature, and expecting further high hardness. Examples of the cyclic fluorinated olefins (3) include monomers (3-1) having an aliphatic cyclic structure and cyclopolymerizable diene monomers (3-2).

[0123] (3-1) Monomers having an aliphatic ring structure

[0124] The above-mentioned monomer (3-1) having an aliphatic cyclic structure is a monomer having an aliphatic cyclic structure in which at least one of the carbon atoms constituting the ring is a carbon atom constituting a carbon-carbon unsaturated double bond. The aliphatic ring in the monomer having an aliphatic cyclic structure is preferably a ring having an ether bond, and more preferably a monomer having no hydrogen atom bonded to a carbon atom. The monomer having an aliphatic cyclic structure is a monomer having a double bond between adjacent carbon atoms constituting the ring (for example, the following formulas (a), (c), (a-1) to (a-5)), or a monomer having a double bond between a carbon atom constituting the ring and a carbon atom outside the ring (for example, the following formulas (a-6) and (a-7)).

[0125] [Chemistry 12]

[0126]

[0127] [Where R 12 ~R 15 Each independently represents a fluorine atom, a C1-C5 perfluoroalkyl group, or a C1-C5 perfluoroalkoxy group.]

[0128] [Chemistry 13]

[0129]

[0130] [Where R 16 ~R 19 Each independently represents a fluorine atom, a C1-C5 perfluoroalkyl group, or a C1-C5 perfluoroalkoxy group.]

[0131] [Chemistry 14]

[0132]

[0133] As the monomer (3-1) having an aliphatic cyclic structure, at least one monomer selected from the group consisting of monomers represented by (a-1), (a-3), (a-6) and (a-7) is particularly preferred, and at least one monomer selected from the group consisting of monomers represented by (a-1), (a-3) and (a-7) is more preferred.

[0134] (3-2) Cyclopolymerizable Diene Monomer

[0135] The cyclopolymerizable diene monomer (3-2) is a cyclopolymerizable diene fluorine-containing monomer. For example, the following formula (b) may be mentioned:

[0136] CF2=CF-Q 1 -CF=CF2…(b)

[0137] [Where Q 1 The monomer is a straight-chain or branched perfluoroalkylene group having 1 to 5 (preferably 1 to 3) carbon atoms, which may have an ether bond and may have a portion of fluorine atoms substituted by halogen atoms other than fluorine atoms. Examples of the halogen atoms other than fluorine atoms include chlorine atoms, bromine atoms, and the like.

[0138] The above Q 1 Preferably, it is a perfluoroalkylene with an ether bond. In this case, the ether bond in the perfluoroalkylene may be present at one end of the group, at both ends of the group, or between carbon atoms of the group. From the aspect of excellent cyclopolymerization, it is preferably present at one end of the group. As the monomer shown in formula (b), perfluoro (3-butenyl vinyl ether), perfluoro (allyl vinyl ether), perfluoro (3,5-dioxaheptadiene), perfluoro (3,5-dioxa-4,4-dimethylheptadiene) etc. can be cited. Perfluoro (3-butenyl vinyl ether) is particularly preferred.

[0139] In addition, as units formed by cyclopolymerization of the monomer represented by the above formula (b), the following formulas (II-1) to (II-4) can be cited. As shown in the following formulas, in formulas (II-1) to (II-3), the four carbon atoms constituting the two double bonds constitute the main chain of the polymer, and in formula (II-4), only the two carbon atoms at the ends of the two double bonds constitute the main chain of the polymer. In addition, as shown in formula (II-1), among the four carbon atoms constituting the two double bonds, two can be connected to Q 1 Together they form an aliphatic ring, as shown in formula (II-2) and formula (II-3), the three double bonds can be 1 Together they form an aliphatic ring, as shown in formula (II-4), where the four double bonds can be 1 Together they form an aliphatic ring. 1The aliphatic ring of cyclopentane easily generates a 5-membered ring and a 6-membered ring, and the polymer generated by cyclopolymerization becomes a polymer having a unit having a 5-membered ring or a 6-membered ring as a main unit.

[0140] [Chemistry 15]

[0141]

[0142] The fluorinated olefin is preferably at least one selected from the group consisting of fluorinated olefins having a functional group (1), fluorinated olefins not containing a functional group (2) and cyclic fluorinated olefins (3). More preferably, it is at least one selected from the group consisting of fluorinated olefins not containing a functional group (2) and cyclic fluorinated olefins (3). Still more preferably, it is cyclic fluorinated olefins (3).

[0143] As the above-mentioned fluorine-containing monomer, the following general formula is also preferred:

[0144] CX 1 X 2 =CY 1 Z 1

[0145] (Where X 1 , X 2 and Y 1 Z is independently H, CH3, F or Cl. 1 The following formula:

[0146] [Chemistry 16]

[0147]

[0148] (Where X 6 ~X 10 (independently a hydrogen atom, a fluorine atom, or a hydrocarbon group having 1 to 8 carbon atoms which may be substituted with fluorine or chlorine). 1 , X 2 , Y 1 and Z contains one or more F. ) is a fluorinated styrene monomer.

[0149] From the perspective of heat resistance, the above-mentioned hydrocarbon group having 1 to 8 carbon atoms which may be substituted by fluorine or chlorine is preferably a hydrocarbon group having 1 to 4 carbon atoms which may be substituted by fluorine, more preferably a hydrocarbon group having 1 to 2 carbon atoms which may be substituted by fluorine, and most preferably -CF3 or CH3.

[0150] As the above-mentioned fluorine-containing styrene monomer, it is preferred to select at least one of the group consisting of CH2=CH-C6F5, CF2=CF-C6H5, CH2=C(CH3)-C6F5, CF2=CF-C6H4-CH3 and CF2=CF-C6H4-CF3, among which, it is more preferred to select at least one of the group consisting of CH2=CH-C6F5 and CF2=CF-C6H5.

[0151] The fluorine-containing monomer is preferably at least one selected from the group consisting of fluorine-containing acrylic monomers, fluorine-containing styrene monomers and fluorine-containing olefins, and more preferably a fluorine-containing acrylic monomer. For example, it is preferably at least one selected from the group consisting of fluoroalkyl acrylates, fluoroalkyl methacrylates, 2-fluoroalkyl acrylates and 2-chlorofluoroalkyl acrylates.

[0152] The above-mentioned fluorine-containing monomer is more preferably of the following general formula (C 1 ):

[0153] CH2=CX 3 -COORf 2 (C 1 )

[0154] (Where X 3 Rf is H, CH3, F, Cl or CF3. 2 It is a fluorinated alkyl group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms. 1 ).

[0155] From the perspective of aggregation, X 3 H, CH 3 or F is preferred. From the viewpoint of heat resistance, CH 3 or F is more preferred. From the viewpoint of monomer stability, CH 3 is further preferred.

[0156] From the perspective of electrical properties and heat resistance, Rf 2 The number of carbon atoms in the moiety is preferably 1-10, more preferably 2-8, and even more preferably 2-6.

[0157] As the above-mentioned fluorinated acrylic monomer (C 1 ), which can be exemplified

[0158] CH2=C(CH3)COOCH2CF3(3FM),

[0159] CH2=C(CH3)COOCH2CF2CF2H(4FM)、

[0160] CH2=C(CH3)COOCH2CF2CF3(5FM)、

[0161] CH2=C(CH3)COOCH2CF2CFHCF3(6FM),

[0162] CH2=C(CH3)COOCH2(CF2)3CF2H(8FM),

[0163] CH2=C(CH3)COOCH2CH2(CF2)3CF3(9FM),

[0164] CH2=C(CH3)COOCH2(CF2)5CF2H(12FM),

[0165] CH2=C(CH3)COOCH2CH2(CF2)5CF3(13FM),

[0166] CH2=C(CH3)COOCH(CF3)2(HFIP-MA)、

[0167] CH2=C(CH3)COOCH2CCH3(CF3)2(6FNP-M),

[0168] CH2=C(CH3)COOCH2CF(CF3)OCF2CF2CF3(6FOn0-MA),

[0169] And the corresponding acrylates, 2-fluoroacrylates and 2-chloroacrylates.

[0170] Examples of the 2-fluoroalkyl acrylate include:

[0171] CH2=CFCOOCH2CF3(3FF)

[0172] CH2=CFCOOCH2CF2CF2H(4FF),

[0173] CH2=CFCOOCH2CF2CF3(5FF),

[0174] CH2=CFCOOCH2(CF2)3CF2H(8FF)、

[0175] CH2=CFCOOCH2CH2(CF2)3CF3(9FF)、

[0176] CH2=CFCOOCH2(CF2)5CF2H(12FF)、

[0177] CH2=CFCOOCH2CH2(CF2)5CF3(13FF)、

[0178] CH2=CFCOOCH(CF3)2(HFIP-F)、

[0179] CH2=CFCOOCH2CCH3(CF3)2(6FNP-F), etc.

[0180] Examples of the above-mentioned 2-chlorofluoroalkyl acrylate include

[0181] CH2=C(Cl)COOCH2CH2(CF2)3CF3(9FCLA),

[0182] CH2=C(Cl)COOCH2CH2(CF2)5CF3(13FCLA) etc.

[0183] Examples of the fluoroalkyl acrylate include

[0184] CH2=CHCOOCH2(CF2)3CF2H(8FA)、

[0185] CH2=CHCOOCH2CH2(CF2)3CF3(9FA)、

[0186] CH2=CHCOOCH2(CF2)5CF2H(12FA)、

[0187] CH2=CHCOOCH2CH2(CF2)5CF3(13FA)、

[0188] CH2=CHCOOCH(CF3)2(HFIP-A),

[0189] CH2=CHCOOCH2CCH3(CF3)2(6FNP-A), etc.

[0190] From the aspects of heat resistance and electrical properties, the above-mentioned fluorinated monomer is preferably a fluorinated olefin, more preferably at least one selected from the group consisting of monomers represented by (a-1), (a-3), (a-6) and (a-7), and further preferably at least one selected from the group consisting of monomers represented by (a-1), (a-3) and (a-7).

[0191] The fluorine content of the above-mentioned fluorine-containing monomer is preferably 30% by mass or more. According to the manufacturing method of the present invention, even when a fluorine-containing monomer having a fluorine content of 30% by mass or more is used, hollow particles with a large average particle size can be manufactured. The fluorine content of the fluorine-containing monomer is more preferably 40% by mass or more, and further preferably 50% by mass or more. In addition, the upper limit of the fluorine content is not particularly limited, and the fluorine content can be 80% by mass, preferably 75% by mass or less, and more preferably 70% by mass or less.

[0192] As the above-mentioned fluorine-containing monomer, at least one selected from the group consisting of 3FM, 5FM, 13FM, HFIP-A, HFIP-MA, HFIP-F, 3FF, 5FF, 13FF, 6FNP-A, 6FNP-M and 6FNP-F is particularly preferred, and at least one selected from the group consisting of 3FM, 5FM, 13FM, 3FF, 5FF, 13FF, HFIP-MA, HFIP-F and HFIP-A is more preferred.

[0193] The solution comprising the fluorinated monomer, the phase separation accelerator and the non-polymerizable solvent preferably further contains a monomer copolymerizable with the fluorinated monomer.

[0194] Examples of the monomer copolymerizable with the fluorine-containing monomer include a crosslinking monomer and a non-fluorine-containing monomer (excluding a crosslinking monomer).

[0195] Examples of the crosslinkable monomer include polyfunctional monomers having two or more (particularly 2 to 4) polymerizable reaction groups, particularly polymerizable double bonds. The use of polyfunctional monomers can improve the strength of the obtained hollow fine particles. The solution preferably further contains a crosslinkable monomer.

[0196] Examples of the polyfunctional monomer include di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and trimethylolpropane di(meth)acrylate; tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, and pentaerythritol tri(meth)acrylate; diallyl compounds or triallyl compounds such as pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, diallyl phthalate, diallyl maleate, diallyl fumarate, diallyl succinate, and triallyl isocyanurate; and divinyl compounds such as divinylbenzene and butadiene.

[0197] Among them, at least one selected from the group consisting of di(meth)acrylates, tri(meth)acrylates and divinyl compounds is preferred, and at least one selected from the group consisting of ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate and divinylbenzene is preferred. These monomers can be used alone or in combination of two or more.

[0198] In addition, from the perspective of improving electrical properties, a fluorine-containing multifunctional acrylate monomer in which a part of the above-mentioned multifunctional acrylate monomer is substituted with fluorine is also preferred. Examples of such fluorine-containing multifunctional acrylate monomers include di-α-fluoroacrylates such as ethylene glycol di-α-fluoroacrylate, diethylene glycol di-α-fluoroacrylate, triethylene glycol di-α-fluoroacrylate, 1,6-hexanediol di-α-fluoroacrylate, and trimethylolpropane di-α-fluoroacrylate; tri-α-fluoroacrylates such as trimethylolpropane tri-α-fluoroacrylate, ethylene oxide-modified trimethylolpropane tri-α-fluoroacrylate, and pentaerythritol tri-α-fluoroacrylate; pentaerythritol tetra-α-fluoroacrylate, dipentaerythritol hexa-α-fluoroacrylate, CH2=CX-COO-CH2(CF2CF2) n CH2-OCO-CX=CH2 (where X is H, CH3, F or Cl, n=1 to 10), CH2=CX-COO-CH2CF(CF3)-O-(CF2CF(CF3)O) n CF(CF3)CH2-OCO-CX=CH2 (where X is H, CH3, F or Cl, n=1 to 20), etc. In addition, CF2=CF-O-(CF2) can also be mentioned. n -O-CF=CF2 (in the formula, n=1~20), CF2=CF-(O-CF2CF(CF3)) n -O-CF=CF2 (in the formula, n=1~20), CF2=CF-(CF2) n -CF=CF2 (wherein n=1~20), etc.

[0199] The non-fluorine-containing monomer (excluding the crosslinking monomer) is not particularly limited, and examples thereof include monofunctional monomers containing no fluorine atom and having one polymerizable reactive group.

[0200] Examples of the monofunctional monomer include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, cumyl (meth)acrylate, cyclohexyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, and isobornyl (meth)acrylate; and (meth)acrylonitrile, (meth)acrylamide, (meth)acrylic acid, glycidyl (meth)acrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. (Meth) acrylic monomers containing polar groups, such as styrene, α-methylstyrene, p-methylstyrene, p-chlorostyrene, and other aromatic vinyl monomers; vinyl acetate, vinyl benzoate, vinyl neononanoate (trade name: Beova 9), vinyl neodecanoate (trade name: Beova 10), vinyl propionate, and other vinyl esters; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, butyl vinyl ether, and hydroxybutyl vinyl ether; halogen-containing monomers such as vinyl chloride and vinylidene chloride; vinyl pyridine, 2-acryloyloxyethylphthalic acid, itaconic acid, fumaric acid, ethylene, propylene, polydimethylsiloxane macromonomers, and the like. Among them, from the perspective of high compatibility with fluorine-containing monomers and high Tg, at least one selected from the group consisting of methyl methacrylate, 2-hydroxyethyl methacrylate, cyclohexyl methacrylate, and isobornyl methacrylate is preferred.

[0201] In the solution, the content of the monomer is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and even more preferably 0.8 to 3.5 parts by mass, based on 1 part by mass of the non-polymerizable solvent.

[0202] The content of the above monomers refers to the amount of the fluorine-containing monomer when only the fluorine-containing monomer is polymerized, and refers to the total amount of the fluorine-containing monomer and the monomer copolymerizable with the fluorine-containing monomer when the fluorine-containing monomer and the monomer copolymerizable with the fluorine-containing monomer are polymerized.

[0203] In the above solution, the ratio of the fluorine-containing monomer and the monomer copolymerizable with the fluorine-containing monomer (crosslinking monomer and non-fluorine-containing monomer) may be appropriately set depending on the target fluorine-containing resin.

[0204] The phase separation accelerator is not limited as long as it can promote phase separation in the polymerization step, and is preferably a polymer, and preferably has a weight average molecular weight of 3,000 or more.

[0205] The weight average molecular weight can be determined from the PS-equivalent weight average molecular weight in GPC measurement.

[0206] The phase separation promoter is preferably a compound that is soluble in a non-polymerizable solvent at room temperature (eg, 25° C.), and the Sp value of the phase separation promoter is SA (J / cm 3 ) 1 / 2 , the Sp value of the non-polymerizable solvent is set to SB (J / cm 3 ) 1 / 2 When , the following formula is satisfied:

[0207] │SA-SB│<3(J / cm 3 ) 1 / 2 The above |SA-SB| of the above phase separation promoter is more preferably less than 2, and further preferably less than 1.

[0208] Examples of the phase separation accelerator include aromatic vinyl polymers, polyalkyl (meth)acrylates, vinyl chloride polymers, polyvinyl acetate, and polyesters.

[0209] Examples of the aromatic vinyl polymer include polystyrene, divinylbenzene, and acrylonitrile-styrene resins, and polystyrene is particularly preferred.

[0210] Examples of the polyalkyl (meth)acrylate include polymethyl methacrylate, polybutyl methacrylate, polyethyl methacrylate, and the like, and polymethyl methacrylate is particularly preferred.

[0211] From the perspective of solubility and hydrophobicity, the phase separation promoter preferably comprises a compound based on the following general formula:

[0212] CH2=CX 4 Y 2

[0213] (Where X 4 Y is H, CH3, F, Cl or CF3. 2 Cl, C6H4R 1 、C6H3R 2 R 3 、COOR 4 or OCOR 5 (Here, R 1 , R 2 , R 3 , R 4 and R 5 Each of the following groups is independently H, OH or an alkyl group having 1 to 40 carbon atoms which may be substituted with a halogen atom. ) A polymer of a polymerized unit of a monomer represented by ).

[0214] In the solution, the content of the phase separation accelerator is preferably 0.01 to 0.5 parts by mass, more preferably 0.02 to 0.3 parts by mass, and even more preferably 0.05 to 0.2 parts by mass, based on 1 part by mass of the non-polymerizable solvent.

[0215] The solution preferably further contains an initiator. The initiator may be added to the solution before the dispersion step, or may be added to the dispersion after the dispersion step and before the polymerization step.

[0216] Examples of the initiator include oil-soluble initiators which initiate polymerization of the fluorinated monomer (or the fluorinated monomer and a monomer copolymerizable with the fluorinated monomer) in droplets formed by dispersing the solution in water. Conventionally used oil-soluble initiators may be used.

[0217] Examples of free radical polymerization initiators include azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(N-butyl-2-methylpropionamide), and other azo compounds, cumene hydroperoxide, tert-butyl hydroperoxide, dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, lauroyl peroxide, and other peroxides that are soluble in monomers. In addition, photopolymerization initiators that initiate polymerization by the action of light such as ultraviolet rays can be used. Such photopolymerization initiators are not particularly limited, and photopolymerization initiators that have been used in the past can be used.

[0218] The initiator is preferably at least one selected from the group consisting of azo compounds, preferably an azo compound, and among them, preferably at least one selected from the group consisting of 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and azobisisobutyronitrile, and more preferably 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile).

[0219] As the non-polymerizable solvent, a solvent that can dissolve the fluorinated monomer and the phase separation promoter, and the monomers, initiators, etc. that can be copolymerized with the fluorinated monomer and used as needed and has low compatibility with the obtained fluorinated resin can be used. By making it have low compatibility with the obtained fluorinated resin, the phase separation of the obtained fluorinated resin can be promoted, and the manufacture of hollow particles can be carried out.

[0220] As the non-polymerizable solvent, a solvent which can dissolve the fluorinated monomer and the phase separation accelerator and, if necessary, a monomer copolymerizable with the fluorinated monomer, an initiator, etc., but does not dissolve the obtained fluorinated resin is more preferably used.

[0221] As the non-polymerizable solvent, the following solvents can be used: a solvent having low compatibility with the fluorine-containing resin and having a low interfacial tension (γ X ) and interfacial tension (γ P )(mN / m), γ X ≥γ P The condition is established, the interfacial tension (γ X ) is the interfacial tension between the non-polymerizable solvent and water, and the interfacial tension (γ P ) is the interfacial tension between the polymer adsorption surface obtained by dissolving the fluorinated monomer (and a monomer copolymerizable with the fluorinated monomer, if necessary) in a non-polymerizable solvent and subjecting the obtained solution to polymerization under the conditions of the production method of the present invention and water.

[0222] As the above-mentioned non-polymerizable solvent, for example, it is preferred that the solvent is liquid at the polymerization temperature of the above-mentioned monomer (fluorine-containing monomer, or fluorine-containing monomer and monomer copolymerizable with fluorine-containing monomer), can be mixed with the monomer but not react with the monomer, and can be easily evaporated by heating, etc., and is preferably at least one selected from the group consisting of aromatic hydrocarbons, esters, or saturated hydrocarbons, or their halogen substitutes.

[0223] Examples of the saturated hydrocarbons and halogen-substituted products thereof include butane, pentane, hexane, hexadecane, cyclohexane, decane, methyl chloride, dichloromethane, chloroform, carbon tetrachloride, bromonaphthalene, and dichloromethane.

[0224] Examples of the aromatic hydrocarbons include toluene, xylene, benzene, and chlorobenzene.

[0225] Examples of the ester include ethyl acetate and butyl acetate.

[0226] In addition, if the compatibility with the fluorine-containing resin is low, fluorine-containing solvents such as fluorine-containing alkanes, fluorine-containing halogenated alkanes, fluorine-containing aromatic compounds and fluorine-containing ethers (such as hydrofluoroether (HFE)) are also preferred. For example, perfluorohexane, 1,3-trifluorotoluene, perfluorotriheptylamine, perfluorotributylamine, etc. are suitable.

[0227] The fluorinated solvent is preferably at least one selected from perfluoroaromatic compounds, perfluorotrialkylamines, perfluoroalkanes, hydrofluorocarbons, perfluorocyclic ethers and hydrofluoroethers. These fluorinated solvents are particularly suitable when using fluorinated olefins, especially PF-MMD.

[0228] The above-mentioned perfluoro aromatic compound is, for example, a perfluoro aromatic compound that may have one or more perfluoroalkyl groups. The aromatic ring possessed by the perfluoro aromatic compound may be at least one ring selected from the group consisting of a benzene ring, a naphthalene ring and an anthracene ring. The perfluoro aromatic compound may have one or more (for example, 1, 2 or 3) aromatic rings. The perfluoroalkyl group as a substituent is, for example, a linear or branched C1-C6, C1-C5 or C1-C4 perfluoroalkyl group, preferably a linear or branched C1-C3 perfluoroalkyl group. The number of substituents is, for example, 1 to 4, preferably 1 to 3, and more preferably 1 to 2. When there are two or more substituents, they may be the same or different. Examples of perfluoro aromatic compounds include perfluorobenzene, perfluorotoluene, perfluoroxylene, and perfluoronaphthalene. Preferred examples of perfluoro aromatic compounds include perfluorobenzene and perfluorotoluene.

[0229] The perfluorotrialkylamine is, for example, an amine substituted with three straight-chain or branched perfluoroalkyl groups. The number of carbon atoms of the perfluoroalkyl group is, for example, 1 to 10, preferably 1 to 5, and more preferably 1 to 4. The perfluoroalkyl groups may be the same or different, preferably the same. Examples of the perfluorotrialkylamine include perfluorotrimethylamine, perfluorotriethylamine, perfluorotripropylamine, perfluorotriisopropylamine, perfluorotributylamine, perfluorotri-sec-butylamine, perfluorotri-tert-butylamine, perfluorotripentylamine, perfluorotriisopentylamine, and perfluorotripentylamine, preferably perfluorotripropylamine or perfluorotributylamine.

[0230] The perfluoroalkane is, for example, a linear, branched or cyclic C3-C12 (preferably C3-C10, more preferably C3-C6) perfluoroalkane. Examples of perfluoroalkane include perfluoropentane, perfluoro-2-methylpentane, perfluorohexane, perfluoro-2-methylhexane, perfluoroheptane, perfluorooctane, perfluorononane, perfluorodecane, perfluorocyclohexane, perfluoro(methylcyclohexane), perfluoro(dimethylcyclohexane) (e.g., perfluoro(1,3-dimethylcyclohexane)), and perfluorodecalin, preferably perfluoropentane, perfluorohexane, perfluoroheptane or perfluorooctane.

[0231] The hydrofluorocarbon is, for example, a C3-C8 hydrofluorocarbon. Examples of hydrofluorocarbons include CF3CH2CF2H, CF3CH2CF2CH3, CF3CHFCHFC2F5, 1,1,2,2,3,3,4-heptafluorocyclopentane, CF3CF2CF2CF2CH2CH3, CF3CF2CF2CF2CF2CHF2, CF3CF2CF2CF2CF2CF2CH2CH3, preferably CF3CH2CF2H or CF3CH2CF2CH3.

[0232] The above-mentioned perfluorocyclic ether is, for example, a perfluorocyclic ether which may have one or more perfluoroalkyl groups. The ring possessed by the perfluorocyclic ether may be a 3- to 6-membered ring. The ring possessed by the perfluorocyclic ether may have one or more oxygen atoms as ring-constituting atoms. The ring preferably has 1 or 2 oxygen atoms, more preferably 1 oxygen atom. The perfluoroalkyl group as a substituent is, for example, a linear or branched C1-C6, C1-C5, or C1-C4 perfluoroalkyl group. The preferred perfluoroalkyl group is a linear or branched C1-C3 perfluoroalkyl group. The number of substituents is, for example, 1 to 4, preferably 1 to 3, more preferably 1 to 2. When there are two or more substituents, they may be the same or different. Examples of perfluorocyclic ethers include perfluorotetrahydrofuran, perfluoro-5-methyltetrahydrofuran, perfluoro-5-ethyltetrahydrofuran, perfluoro-5-propyltetrahydrofuran, perfluoro-5-butyltetrahydrofuran, and perfluorotetrahydropyran. Preferred examples of perfluorocyclic ethers include perfluoro-5-ethyltetrahydrofuran and perfluoro-5-butyltetrahydrofuran.

[0233] The hydrofluoroether is, for example, a fluorine-containing ether. The global warming potential (GWP) of the hydrofluoroether is preferably 400 or less, more preferably 300 or less. Examples of the hydrofluoroether include CF3CF2CF2CF2OCH3, CF3CF2CF(CF3)OCH3, CF3CF(CF3)CF2OCH3, CF3CF2CF2CF2OC2H5, CF3CH2OCF2CHF2, C2F5CF(OCH3)C3F7, trifluoromethyl 1,2,2,2-tetrafluoroethyl ether (HFE-227me), difluoromethyl 1,1,2,2,2-pentafluoroethyl ether (HFE-227mc), trifluoromethyl 1,1,2,2-tetrafluoroethyl ether (HFE-227pc), difluoromethyl 2,2,2-trifluoroethyl ether (HFE-245mf), and 2,2-difluoroethyl trifluoromethyl ether (HFE-245pf). As the hydrofluoroether, CF3CH2OCF2CHF2, C2F5CF(OCH3)C3F7; CF3CF2CF2CF2OCH3, CF3CF2CF2CF2OC2H5 and the like are preferred.

[0234] R 21 -OR 22 (D1)

[0235] [Where R 21 is a straight-chain or branched perfluorobutyl group, R 22 is methyl or ethyl.], and more preferably the compound represented by the above formula (D1).

[0236] From the perspective of producing hollow particles with a single-pore structure, the non-polymerizing solvent is more preferably at least one selected from the group consisting of aromatic hydrocarbons, esters, or saturated hydrocarbons having 8 to 18 carbon atoms, or their halogen-substituted products, further preferably at least one selected from the group consisting of toluene and xylene, and particularly preferably toluene.

[0237] In the production method of the present invention, by changing the type of non-polymerizable solvent, a single-porous structure or a porous structure can be formed. The reason for forming a porous structure or a single-porous structure is not yet clear, but in the combination of the generated fluorine-containing resin and the solvent, a completely incompatible system has a single-porous structure, and a slightly compatible system shows a porous structure.

[0238] The completely incompatible system can be any system in which the generated fluorine-containing resin is 5% by mass in the non-polymerizable solvent and visually does not swell after 6 hours at the polymerization temperature. For example, hollow particles with a single-pore structure can be produced by using the above-mentioned saturated hydrocarbons as the non-polymerizable solvent.

[0239] The amount of the non-polymerizable solvent used can be appropriately selected from a wide range and is generally preferably 0.1 to 10 parts by mass, particularly preferably 0.5 to 5 parts by mass, relative to 1 part by mass of the monomer (i.e., the fluorine-containing monomer, or the fluorine-containing monomer and a monomer copolymerizable with the fluorine-containing monomer).

[0240] The solution preferably further contains a dispersion stabilizer. By containing a dispersion stabilizer, phase separation can be further promoted, and hollow fine particles having a large particle size can be obtained.

[0241] As the dispersion stabilizer, a wide range of substances that have a function of preventing droplets formed by dispersing a solution containing a monomer component, a phase separation accelerator, and a non-polymerizable solvent in water from coalescing.

[0242] Examples include high molecular weight dispersion stabilizers such as polyvinyl alcohol, methylcellulose, ethylcellulose, polyacrylic acid, polyacrylimide, polyethylene oxide, poly(hydroxystearic acid-g-methyl methacrylate-co-methacrylic acid) copolymer, nonionic surfactants, anionic surfactants, amphoteric surfactants, etc. Among them, high molecular weight dispersion stabilizers such as polyvinyl alcohol are preferred. In addition, fluorinated anionic surfactants, etc. may also be used.

[0243] The content of the dispersion stabilizer is preferably 0.005 to 1 part by mass, more preferably 0.01 to 0.1 part by mass, based on 1 part by mass of the solution.

[0244] The dispersing step is a step of dispersing a solution containing a fluorinated monomer, a phase separation accelerator, a non-polymerizable solvent, and, if necessary, a monomer copolymerizable with the fluorinated monomer, an initiator, a dispersion stabilizer, etc., in water to obtain a dispersion.

[0245] As a dispersion method, various known methods such as a dispersion method based on mechanical shear force such as a homogenizer or a membrane emulsification method can be used. The temperature condition during dispersion can be above 0°C and below 100°C, preferably 0 to 90°C. When the above-mentioned solution in the dispersion step contains an initiator, it is necessary to be below the temperature that affects the decomposition of the initiator used, usually below room temperature, particularly preferably around 0 to 30°C.

[0246] In the above dispersion method, the size of the droplets formed by dispersing the above solution is not monodispersed, but usually various droplets of different particle sizes are mixed. Therefore, the hollow fine particles finally obtained also have different particle sizes.

[0247] On the other hand, it is also possible to obtain monodisperse droplets by selecting a dispersion method to make the size of the droplets uniform. As a method for obtaining such monodisperse droplets, for example, a method for preparing monodisperse droplets by a membrane emulsification method using porous glass (SPG) can be cited. In the case of preparing such monodisperse droplets with uniform particle size, the hollow microparticles finally obtained also form a monodisperse with uniform particle size.

[0248] In either case, the average particle size of the droplets may be appropriately determined according to the desired average particle size of the hollow fine particles.

[0249] The above-mentioned dispersing step is also preferably: a dispersing step A, dispersing the above-mentioned solution in water at a temperature of 50°C or higher (preferably 55°C or higher, more preferably 60°C or higher, and further preferably 65°C or higher) to obtain a dispersion; or a dispersing step B, dispersing the above-mentioned solution in water at a temperature lower than 50°C to obtain a dispersion, and heating the obtained dispersion to a temperature of 50°C or higher (preferably 55°C or higher, more preferably 60°C or higher, and further preferably 65°C or higher). By adopting the above-mentioned steps, even when the fluorine content of the fluorine-containing monomer is high, the dispersion does not phase separate, and polymerization can be efficiently performed.

[0250] The production method of the present invention also preferably further includes a step of adding an oil-soluble initiator to the above-mentioned dispersion liquid after the dispersion step and before the polymerization step. As described above, when the dispersion step is performed at a relatively high temperature (for example, above 50° C.), if the initiator is added to the above-mentioned solution in advance, polymerization may start during the dispersion step. Therefore, by further adding the initiator to the above-mentioned dispersion liquid after the dispersion step and before the polymerization step, the dispersion step can also be performed at a relatively high temperature.

[0251] The polymerization step may be performed so long as at least the fluorine-containing monomer is polymerized. Only the fluorine-containing monomer may be polymerized, or the fluorine-containing monomer and a monomer copolymerizable with the fluorine-containing monomer may be polymerized.

[0252] In the above-mentioned polymerization step, a method based on the polymerization method known in the art such as microemulsion polymerization, miniemulsion polymerization, microsuspension polymerization, etc. can be used. The polymerization in the above-mentioned polymerization step can also be suspension polymerization. In order to subject the dispersion liquid in which the above-mentioned solution is dispersed to suspension polymerization, the dispersion liquid can be heated under stirring.

[0253] The polymerization temperature is not particularly limited as long as it is a temperature sufficient to initiate polymerization of the fluorinated monomer (and a monomer copolymerizable with the fluorinated monomer if necessary) by the initiator, and is usually 10 to 90°C, particularly preferably 30 to 80°C.

[0254] The polymerization is carried out until the desired hollow fine particles are obtained. The time required for the polymerization varies depending on the types of the fluorinated monomer (and monomers copolymerizable with the fluorinated monomer used as required), the polymerization initiator, and the non-polymerizable solvent used, but is generally about 3 to 24 hours.

[0255] Furthermore, during the polymerization, it is preferably carried out under an inert gas atmosphere such as nitrogen or argon.

[0256] By performing polymerization in this way, the fluorine-containing monomer (or the fluorine-containing monomer and the monomer copolymerizable with the fluorine-containing monomer) is polymerized in the droplets of the solution containing the fluorine-containing monomer (or the fluorine-containing monomer and the monomer copolymerizable with the fluorine-containing monomer), the phase separation accelerator and the non-polymerizable solvent.

[0257] In the obtained polymer, the phase separation is promoted by the presence of the phase separation promoter and the non-polymerizable solvent, and as a result, a shell of a single-layer structure is formed, that is, a shell containing a fluorine-containing resin containing a polymerized unit based on a fluorine-containing monomer (or a polymerized unit based on a fluorine-containing monomer and a monomer copolymerizable with the fluorine-containing monomer). On the other hand, the core portion as a hollow portion is in a state of enclosing a non-polymerizable solvent.

[0258] The hollow fine particles thus obtained may be used directly in the state of a dispersion, or may be filtered and, if necessary, washed with water and then provided in the form of a powder for various purposes.

[0259] Furthermore, the hollow fine particles in the form of a dispersion or a powder can be provided for various applications in the form of removing the non-polymerizable solvent. Therefore, the method for producing hollow fine particles of the present invention preferably further comprises a step of removing the non-polymerizable solvent from the obtained hollow fine particles.

[0260] The removal process is not particularly limited as long as it is a method that can remove the non-polymerizable solvent present in the hollow part, and examples thereof include a method of heating the hollow fine particles having the non-polymerizable solvent in the hollow part, a method of naturally evaporating the non-polymerizable solvent, and a decompression treatment. From the perspective of simplicity and economy, it is preferably removed by heating, and the heating temperature can be appropriately set according to the non-polymerizable solvent, etc., and is preferably heated at a temperature of 20° C. to 300° C. and a pressure of about 1 Pa to 100,000 Pa.

[0261] In the present invention, the hollowness of hollow fine particles includes not only the case where air exists in the hollow part, but also the case where the above-mentioned non-polymerizable solvent and the like exist in the hollow part.

[0262] By having the above-mentioned structure, the manufacturing method of the present invention can manufacture hollow microparticles with an average particle diameter of 1.0 μm or more. The average particle diameter of the hollow microparticles is preferably 1.0 μm or more, more preferably 2.0 μm or more, and further preferably 5.0 μm or more. From the aspect of particle stability, the above-mentioned average particle diameter is preferably 50.0 μm or less, and more preferably 30.0 μm or less.

[0263] The average particle size can be measured by DLS (dynamic light scattering) or calculated from optical microscope photographs using particle size analysis software LUZEX AP. In this case, it is preferred to analyze the average particle size by taking a plurality of photographs so that the total number of particles is 50 or more.

[0264] In addition, in the production method of the present invention, the hollow fine particles of the present invention described below can be produced.

[0265] The hollow particles of the present invention contain a fluorine-containing resin D containing polymerized units based on a fluorine-containing monomer, and have an average particle size of 1.0 μm or more. The hollow particles of the present invention may have a so-called shell structure, but preferably consist of a shell containing a fluorine-containing resin D and a hollow part, and have a single-hole structure.

[0266] It should be noted that, in this specification, "single-hole structure" does not include a situation with multiple voids like a porous state, but refers to a structure with only one closed void. In addition, in the following description, the part other than the void of the hollow fine particle is referred to as a "shell".

[0267] The particle size of the hollow fine particles of the present invention can be adjusted by changing the size of the droplets in the above-mentioned production method. However, it is difficult to increase the average particle size of hollow fine particles containing a fluorine-containing resin in conventional methods.

[0268] By using the production method of the present invention, even hollow fine particles containing a fluorine-containing resin can have a large average particle diameter, and hollow fine particles having an average particle diameter of 1.0 μm or more can be produced.

[0269] The average particle size of the hollow fine particles of the present invention is preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 5.0 μm or more. Also, the average particle size is preferably 50.0 μm or less, more preferably 40.0 μm or less, and even more preferably 30.0 μm or less.

[0270] The average particle size can be measured by DLS (dynamic light scattering) or calculated from optical microscope photographs using particle size analysis software LUZEX AP. In this case, it is preferred to analyze the average particle size by taking a plurality of photographs so that the total number of particles is 50 or more.

[0271] The hollow fine particles of the present invention are preferably composed of a shell containing a fluorine-containing resin D and a hollow part, and have a single-hole structure, and the pore size of the hollow part is preferably 66% to 95% relative to the diameter of the hollow fine particles. The pore size of the hollow part is more preferably 66% or more, further preferably 74% or more, and particularly preferably 79% or more relative to the diameter of the hollow fine particles. In addition, it is preferably 95% or less, more preferably 93% or less, further preferably 90% or less, and particularly preferably 88% or less.

[0272] The pore size of the hollow part can be calculated by using the particle size analysis software LUZEX AP to analyze the image of the TEM photo of the hollow particles. Specifically, about 200 hollow particles in the TEM photo are randomly selected and the inner radius (R1) is measured, from which the pore size of the hollow part can be calculated by the following formula.

[0273] Hollow hole diameter = R1×2

[0274] In the hollow particles of the present invention, the ratio of the thickness of the shell of the hollow particles to the diameter is preferably 17% or less. The above ratio is more preferably 13% or less, further preferably 10% or less, and particularly preferably 9% or less. If the thickness of the shell is thin, the porosity increases, so that hollow particles with a lower dielectric constant can be made.

[0275] From the viewpoint of the strength of the hollow fine particles, the above ratio is preferably 4% or more, more preferably 6% or more.

[0276] The thickness of the shell can be calculated by using the particle size analysis software LUZEX AP to analyze the TEM photo of the hollow particles. Specifically, about 200 hollow particles are randomly selected from the TEM photo, and the inner radius (R1) and outer radius (R2) are measured, from which the thickness of the shell can be calculated by the following formula.

[0277] Shell thickness = R2-R1

[0278] The void ratio of the hollow microparticles of the present invention is preferably 30% by volume or more. The void ratio is more preferably 40% by volume or more, further preferably 50% by volume or more, and particularly preferably 55% by volume or more. If the void ratio is high, the relative dielectric constant of the hollow microparticles can be reduced, which is suitable for electrical material purposes. The upper limit of the void ratio is not particularly limited, and from the aspect of the strength of the hollow microparticles, it is preferably 80% by volume or less, more preferably 70% by volume or less.

[0279] The porosity can be calculated by using the particle size analysis software LUZEX AP to analyze the image of the TEM photo of the hollow particles. Specifically, about 200 hollow particles are randomly selected from the TEM photo, and the inner radius (R1) and outer radius (R2) are measured, from which the porosity can be calculated by the following formula.

[0280] Void ratio (%) = (R1 / R2) 3 ×100

[0281] The refractive index of the hollow fine particles of the present invention is preferably 1.40 or less. The refractive index is more preferably 1.35 or less, further preferably 1.30 or less, and particularly preferably 1.25 or less. The lower limit of the refractive index is not particularly limited, and may be, for example, 1.10 or more.

[0282] The above-mentioned refractive index is a value obtained by a liquid immersion method.

[0283] The fluorine-containing resin D may consist only of polymerized units derived from a fluorine-containing monomer, or may contain polymerized units derived from a fluorine-containing monomer and polymerized units derived from a monomer copolymerizable with the fluorine-containing monomer.

[0284] Examples of the monomer copolymerizable with the fluorine-containing monomer include the above-mentioned crosslinking monomers and non-fluorine-containing monomers (excluding the crosslinking monomer).

[0285] The fluorine-containing resin D preferably contains polymerized units based on a fluorine-containing monomer and polymerized units based on a crosslinking monomer, because the shell of the hollow fine particles can be made strong. Since the shell of the hollow fine particles is strong, the shell thickness can be reduced and the porosity can be increased.

[0286] Examples of the crosslinkable monomer include those exemplified in the production method of the present invention, preferably a polyfunctional monomer having two or more polymerizable double bonds, more preferably ethylene glycol di(meth)acrylate and divinylbenzene, and further preferably ethylene glycol di(meth)acrylate.

[0287] In the fluorine-containing resin D, the polymerized units based on the crosslinkable monomer are preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 30% by mass or more relative to all polymerized units. In addition, it is preferably 90% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less. By making the polymerized units based on the crosslinkable monomer within the above range, the obtained hollow fine particles can have excellent strength and excellent electrical properties.

[0288] In the fluorine-containing resin D, the content of polymerized units based on the non-fluorine-containing monomer is preferably from 0 to 70% by mass, more preferably from 0 to 50% by mass, based on all polymerized units.

[0289] The fluorine content of the fluorine-containing resin D is preferably 15% by mass or more. When the fluorine content is 15% by mass or more, the electrical properties and water resistance are more excellent. The fluorine content is more preferably 30% by mass or more, and further preferably 50% by mass or more. Hollow fine particles containing such fluorine-containing resin D and having an average particle size of 1.0 μm or more can be obtained by the production method of the present invention, particularly the production method in which the dispersion step is the dispersion step A or the dispersion step B.

[0290] In the fluorine-containing resin D, examples of the fluorine-containing monomer, the crosslinking monomer and the non-fluorine-containing monomer (excluding the crosslinking monomer) include the same monomers as those used in the production method of the present invention.

[0291] In the fluorine-containing resin D, the fluorine-containing monomer may be a fluorine-containing acrylic monomer, a fluorine-containing styrene monomer, a fluorine-containing olefin, etc., but is not particularly limited. Preferably, the fluorine-containing monomer is a monomer of the following general formula (B 2 ) shown in the monomer (B 2 ).

[0292] CX 1 X 2 =CY 1 Z(B 2 )

[0293] (Where X 1 , X 2 and Y 1 are independently the same or different and are H, CH3, F or Cl. Z is F or -Q-Rf 1 -Y(Q is a single bond, -O-, -O-(C=O)- or -C(=O)-O-. Rf 1 It is a fluorinated alkylene group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms. Y is a group represented by F, H, -OH, -COOH, -COOR (R is an alkyl group having 1 to 20 carbon atoms), or the following formula:

[0294] [Chemistry 17]

[0295]

[0296] (Where X 6 ~X 10 are independently a hydrogen atom, a fluorine atom, or a hydrocarbon group having 1 to 8 carbon atoms which may be substituted with fluorine or chlorine) or -SO3H. 1 , X 2 , Y 1 and Z contain one or more F. ). As the general formula (B 2 ) 1 , X 2 , Y 1 and Z, can be appropriately used in the above general formula (B 1 ) 1 , X 2 , Y 1 The same substance as Z.

[0297] In the above-mentioned fluorine-containing resin D, the fluorine-containing monomer is particularly preferably the following general formula (C 2 ) shown in the fluorinated acrylic monomer (C 2 ).

[0298] CH2=CX 3 -COORf 2 (C 2 )

[0299] (Where X 3 Rf is H, CH3, F, Cl or CF3. 2 It is a fluorinated alkyl group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms.

[0300] As the general formula (C 2 ) 3 and Rf 2 , can be appropriately used with the above general formula (C 1 ) 3 and Rf 2 Same substance.

[0301] As the above-mentioned fluorinated acrylic monomer (C 2 ), and examples thereof include the fluorinated acrylic monomer (C 1 ) the same substance.

[0302] As the above-mentioned fluorine-containing monomer, at least one selected from the group consisting of 3FM, 5FM, 13FM, HFIP-A, 3FF, 5FF, 13FF, HFIP-MA and HFIP-F is particularly preferred, and at least one selected from the group consisting of 3FM, 5FM, 13FM, HFIP-MA and HFIP-A is more preferred.

[0303] The fluorine-containing resin D preferably comprises a fluorine-containing acrylic monomer (C 2 ) and a cross-linkable monomer (E) based on at least one selected from the group consisting of di(meth)acrylates, tri(meth)acrylates and divinyl compounds.

[0304] In the above fluorine-containing resin D, the above fluorine-containing monomer (C 2 ) of the polymerized unit (C 2 ) to the mass ratio of the polymerized units based on the crosslinkable monomer (E) (fluorinated monomer (C 2 ) / crosslinkable monomer (E)) is preferably 80 / 20 to 20 / 80 (mass ratio), more preferably 70 / 30 to 30 / 70 (mass ratio), further preferably 60 / 40 to 40 / 60 (mass ratio).

[0305] From the viewpoint of heat resistance and electrical characteristics, the fluorinated monomer is preferably a fluorinated olefin, preferably at least one selected from the group consisting of a fluorinated olefin having a functional group (1), a fluorinated olefin not containing a functional group (2) and a cyclic fluorinated olefin (3), more preferably at least one selected from the group consisting of a fluorinated olefin not containing a functional group (2) and a cyclic fluorinated olefin (3), and further preferably a cyclic fluorinated olefin (3). In addition, the cyclic fluorinated olefin (3) is preferably at least one selected from the group consisting of the monomers represented by (a-1), (a-3), (a-6) and (a-7), more preferably at least one selected from the group consisting of the monomers represented by (a-1), (a-3) and (a-7).

[0306] The relative dielectric constant (1 kHz) of the fluorine-containing resin D is preferably 5.0 or less. The relative dielectric constant is more preferably 4.0 or less, further preferably 3.7 or less, and particularly preferably 3.5 or less. The lower limit of the relative dielectric constant is not particularly limited, and may be, for example, 1.1 or more.

[0307] The above relative dielectric constant is a value obtained by a measurement method in accordance with JIS C 2138.

[0308] The refractive index of the fluorine-containing resin D is preferably 1.40 or less. The refractive index is more preferably 1.39 or less, and particularly preferably 1.38 or less. The lower limit of the refractive index is not particularly limited, and may be, for example, 1.30 or more, and is preferably 1.35 or more from the perspective of solubility in non-polymerizable solvents.

[0309] The above-mentioned refractive index is a value obtained by a liquid immersion method.

[0310] The hollow particles of the present invention preferably contain a phase separation promoter. As the phase separation promoter, the phase separation promoter described in the method for producing the above-mentioned hollow particles can be cited. By manufacturing the hollow particles by a method using a phase separation promoter as in the method for producing the above-mentioned hollow particles, hollow particles containing the phase separation promoter can be obtained. The above-mentioned phase separation promoter is contained in the shell of the hollow particles.

[0311] The content of the phase separation accelerator is, for example, preferably 50% by mass or less, more preferably 30% by mass or less, and still more preferably 20% by mass or less, based on the fluorine-containing resin D.

[0312] The content of the phase separation accelerator may be 1% by mass or more, or 5% by mass or more, based on the fluorine-containing resin.

[0313] In the hollow fine particles of the present invention, the hollow portion is preferably a gas, more preferably air, from the viewpoint of low dielectric properties and low refractive index.

[0314] Since the hollow fine particles of the present invention are hollow, they are excellent in low dielectric properties and high frequency characteristics, and therefore are suitable for use in electronic materials. That is, the hollow fine particles of the present invention are preferably hollow fine particles for electronic materials.

[0315] The hollow particles of the present invention contain the above-mentioned fluorine-containing resin D, and the average particle diameter is 1.0 μm or more, so the dielectric constant can be reduced, and the surface area when used in the same volume can be reduced, so it is suitable for a resin composition used as a low dielectric material. If the average particle diameter is small, the specific surface area increases, so the electrical properties are significantly reduced due to the influence of moisture attached to the interface, etc.

[0316] In addition, the present invention also provides a resin composition, which is formed by dispersing the hollow particles of the present invention in an insulating resin. The above-mentioned insulating resin is not particularly limited, and examples thereof include fluorine-containing resins, epoxy resins, thermosetting modified polyphenylene ether resins, thermosetting polyimide resins, silicone resins, benzoxazine resins, melamine resins, urea resins, allyl resins, phenolic resins, unsaturated polyester resins, polyurethane resins, aniline resins, etc. Among them, fluorine-containing resins, epoxy resins, thermosetting resins, modified polyphenylene ether resins, thermosetting polyimide resins, silicone resins, benzoxazine resins, and melamine resins, etc., are suitable. These insulating resins can be used alone, or two or more can be used in combination.

[0317] The content of the hollow fine particles in the low dielectric material is not particularly limited and may be appropriately set according to the properties required in various applications. For example, the content may be 10 to 90 parts by mass based on 100 parts by mass of the insulating resin.

[0318] The application of the hollow fine particles and the curable composition of the present invention in electronic materials is not particularly limited, and examples thereof include printed circuit boards, antenna substrates, and interlayer insulating films of high-frequency connector components. They are particularly useful for high-frequency-compatible substrates used in 5G and 6G.

[0319] Since the hollow fine particles of the present invention are hollow, they are excellent in low refractive index and can be used in various applications requiring a low refractive index. That is, the hollow fine particles of the present invention are preferably hollow fine particles for a low refractive material.

[0320] When used as a low-refractive material, it can be suitably used in, for example, an antireflection film, a refractive index adjuster, an additive filler for an optical adhesive, a low-refractive index lens material, a prism, and the like.

[0321] If the hollow particles of the present invention are dispersed in a suitable binder to form an anti-reflection film coating agent, an anti-reflection film can be easily produced. The hollow particles of the present invention have a low refractive index, and are also excellent in alkali resistance and dispersibility to the binder, so the obtained anti-reflection film can effectively suppress the reflection of the transparent substrate, has strong antifouling and cleaning properties, and is also excellent in mechanical strength.

[0322] An antireflection film coating agent containing the hollow fine particles of the present invention and a binder, and an antireflection film formed using the hollow fine particles of the present invention or the antireflection film coating agent of the present invention are also aspects of the present invention.

[0323] The coating agent for an antireflection film of the present invention contains the hollow fine particles of the present invention and a binder.

[0324] The binder is not particularly limited as long as it is a transparent material that can form a film, and both organic materials such as resins and inorganic materials can be used.

[0325] Examples of the organic materials include cellulose derivatives such as triacetyl cellulose, diacetyl cellulose, propionyl cellulose, butyryl cellulose, cellulose acetyl acetate, and cellulose nitrate; polyamides, polycarbonates, polyesters described in Japanese Patent Gazette No. 48-40414 (especially polyethylene terephthalate, poly-1,4-cyclohexanedimethylene terephthalate, polyethylene 1,2-diphenoxyethane-4,4-dicarboxylate, polybutylene terephthalate, polyethylene naphthalate, etc.), polystyrene, polypropylene, polyethylene, polymethylpentene, polysulfone, polyethersulfone, polyarylate, polyetherimide, polymethyl methacrylate, or various fluorine-containing resins thereof, and the like, which are transparent resins with a low refractive index.

[0326] It should be noted that, when a transparent resin is used as the above-mentioned binder, it is preferred to use a transparent resin having a glass transition temperature lower than the glass transition temperature of the hollow particles of the present invention. Thus, the binder acts as an adhesive between the hollow particles during film formation, and sufficient film strength can be obtained.

[0327] As the above-mentioned inorganic materials, for example, alkoxides of various elements, salts of organic acids, and coordination compounds formed by combining with coordination compounds can be mentioned. Specifically, for example, metal alkoxide compounds such as tetraethoxytitanium, tetraisopropoxytitanium, tetra-n-propoxytitanium, tetra-n-butoxytitanium, tetra-sec-butoxytitanium, tetra-tert-butoxytitanium, triethoxyaluminum, triisopropoxyaluminum, tributoxyaluminum, triethoxyantimony, tributoxyantimony, tetraethoxyzirconium, tetraisopropoxyzirconium, tetra-n-propoxyzirconium, tetra-n-butoxyzirconium, tetra-sec-butoxyzirconium, and tetra-tert-butoxyzirconium can be mentioned; chelate compounds such as diisopropoxytitanium diacetylacetonate, dibutoxytitanium diacetylacetonate, diethoxytitanium diacetylacetonate, zirconium diacetylacetonate, aluminum acetylacetonate, di-n-butoxymonoethyl acetylacetate aluminum, diisopropoxymonomethyl acetylacetate aluminum, and tri-n-butoxymonoethyl acetylacetate zirconium can be mentioned; and active inorganic polymers containing ammonium zirconyl carbonate or zirconium as the main component can be mentioned.

[0328] As the mixing ratio of the hollow particles of the present invention and the binder, there is no particular limitation, and the preferred lower limit of the mixing amount of the hollow particles is 5 volume %, and the preferred upper limit is 95 volume %. If it is less than 5 volume %, the refractive index of the obtained anti-reflection film may not be fully reduced, and if it exceeds 95 volume %, the mechanical strength of the obtained anti-reflection film has a time difference. A more preferred lower limit is 30 volume %, a more preferred upper limit is 90 volume %, and a further preferred lower limit is 50 volume %, and a further preferred upper limit is 80 volume %.

[0329] The coating agent for antireflection film of the present invention may be an emulsion in which hollow fine particles are suspended in a binder when a curable binder is used as the binder, and may be a coating agent diluted in an appropriate volatile solvent in other cases.

[0330] The diluent solvent is not particularly limited, and from the perspective of the stability, wettability, volatility, etc. of the composition, suitable examples include alcohols such as methanol, ethanol, isopropanol, butanol, and 2-methoxyethanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as methyl acetate, ethyl acetate, and butyl acetate; ethers such as diisopropyl ether; glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, and butyl carbitol; aliphatic hydrocarbons such as hexane, heptane, and octane; halogenated hydrocarbons; aromatic hydrocarbons such as benzene, toluene, and xylene; N-methylpyrrolidone, dimethylformamide, etc. These diluent solvents may be used alone or in combination of two or more.

[0331] The antireflection film of the present invention can be produced by applying the coating agent for an antireflection film of the present invention onto a release film or the like, or directly onto a transparent substrate, and then drying the coating agent.

[0332] The coating method of the antireflective coating agent of the present invention is not particularly limited, and examples thereof include dip coating, spin coating, flow coating, spray coating, roll coating, gravure roll coating, air knife coating, blade coating, wire wound blade coating, blade coating, reverse coating, transfer roll coating, micro gravure coating, lick coating, cast coating, slot coating, calendar coating, die coating, and the like.

[0333] The coating agent for an antireflection film of the present invention is applied onto a release film or the like, or directly onto a transparent substrate, and then a coating film is formed by heating and drying, and then the coating film is cured by heating, humidification, ultraviolet irradiation, electron beam irradiation, etc., thereby obtaining the antireflection film of the present invention.

[0334] The antireflection film of the present invention preferably has a smooth surface. The term "smooth surface" as used herein means that the surface roughness Rz calculated by the method specified in JIS B0601 is 0.2 μm or less.

[0335] By making the surface smooth, the antireflection film of the present invention does not appear white as a whole due to diffuse reflection of light on the surface, and dirt such as fingerprints, sebum, sweat, and cosmetics are less likely to adhere to the surface, and even if the dirt temporarily adheres, it can be easily removed.

[0336] The antireflection film of the present invention may further have a substrate layer in addition to the layer formed using the antireflection film coating agent of the present invention. By having the substrate layer, the mechanical strength of the antireflection film of the present invention is improved, and the handling property is improved.

[0337] The substrate layer is not particularly limited as long as it is transparent, and from the viewpoint of moldability and mechanical strength, for example, a substrate layer composed of a transparent resin that can be used as the binder is suitable.

[0338] The thickness of the antireflection film of the present invention is not particularly limited, but the preferred lower limit is 0.05 μm and the preferred upper limit is 100 μm. If it is less than 0.05 μm, the scratch resistance may be insufficient, and if it exceeds 100 μm, the film may be easily broken.

[0339] In addition, when the anti-reflection film of the present invention has the above-mentioned substrate layer, the thickness of the substrate layer is not particularly limited, but the preferred lower limit is 50 μm and the preferred upper limit is 500 μm. If it is less than 50 μm, the strength of the anti-reflection film of the present invention may be deteriorated, and if it exceeds 500 μm, the transparency of the anti-reflection film of the present invention may be deteriorated, and it may be difficult to see the visual information inside.

[0340] Example

[0341] Next, the present invention will be described with reference to Examples, but the present invention is not limited to the Examples.

[0342] [Example 1]

[0343] The fluorinated monomer was 2,2,2-trifluoroethyl methacrylate (3FM), the crosslinking monomer was ethylene glycol dimethacrylate (EGDM), and the oil phase solvent was polystyrene (PS) (polymerization degree 2,000) (Sp value 18.4 (J / cm 3 ) 1 / 2 ) as a phase separation promoter toluene solution (Sp value 18.2 (J / cm 3 ) 1 / 2 ), low-temperature initiator 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile) (V-70) as an initiator, and polyvinyl alcohol (PVA) with Pn=1700 and saponification degree=88% as a dispersion stabilizer.

[0344] According to the composition shown in Table 1 below, EGDM as a crosslinking monomer and 3FM as a fluorine-containing monomer were added to a toluene solution in which PS was dissolved at a weight ratio of 1:1, and then a uniform oil phase in which initiator V-70 was dissolved was dispersed in an aqueous medium using a homogenizer to prepare suspended drops. The suspension was polymerized by stirring at 400 rpm at 30°C for 5 hours under a nitrogen atmosphere to prepare hollow fine particles of a fluorine-containing resin.

[0345] Figure 1 (a) shows an optical microscope photograph of the suspended droplets before polymerization. Figure 1 (b) shows an optical microscope photograph of the hollow microparticles after polymerization. In the optical microscope photograph before polymerization, uniform suspended droplets were confirmed. In the optical microscope photograph after polymerization, it is suggested that particles with a hollow structure were obtained. The obtained hollow microparticles were dried, prepared into SEM samples, and observed after being crushed. Figure 2 As shown, it is clear that the sample has a hollow structure even in a dry state. Hereinafter, the sample obtained in Example 1 is referred to as "3FM1:1".

[0346] [Comparative Example 1]

[0347] The polymerization was carried out in the same manner as in Example 1 except that PS and toluene were not added, and as a result, solid particles without a hollow structure were obtained. Hereinafter, the sample obtained in Comparative Example 1 is referred to as "3FM solid".

[0348] [Example 2]

[0349] Polymerization was carried out in the same manner as in Example 1, except that the mass ratio of EGDM as the crosslinking monomer and 3FM as the fluorine-containing monomer was changed to 1:2 (0.22 g:0.44 g), thereby producing hollow fine particles containing a fluorine-containing resin. Figure 3 (a) shows an optical microscope photograph of the suspended droplets before polymerization. Figure 3 (b) shows an optical microscope photograph of the hollow fine particles after polymerization. Although the inner wall of the hollow structure was slightly disordered, it was confirmed that hollow fine particles were obtained as in "3FM1:1". Hereinafter, the obtained sample is referred to as "3FM1:2".

[0350] It should be noted that, for hollow fine particles having a particle size of 10 μm or more, a nested structure in which particles are generated within particles was confirmed to be formed. This is considered to be the result of the precipitation of the polymer before moving to the outermost shell.

[0351] [Example 3]

[0352] Hollow fine particles containing a fluorine-containing resin were prepared by polymerization in the same manner as in Example 1 except that the types and amounts of the components were changed according to the composition shown in Table 1. In Table 1, 5FM is 2,2,3,3,3-pentafluoropropyl methacrylate represented by CH2=C(CH3)COOCH2CF2CF3.

[0353] As a result of optical microscope observation, it was confirmed that hollow fine particles were obtained in the same manner as 3FM used in Examples 1 and 2.

[0354] [Comparative Example 2]

[0355] Hollow microparticles containing fluorine-containing resin were prepared by polymerization in the same manner as in Example 1 except that the types and amounts of the components were changed as shown in Table 1 below and the rotation speed during polymerization was 400 rpm. In Table 1, 13FM is 1H,1H,2H,2H-tridecafluorooctyl methacrylate (13FM) represented by CH2=C(CH3)COOCH2CH2(CF2)5CF3.

[0356] Figure 4 (a) shows an optical microscope photograph of the suspended droplets before polymerization. Figure 4 (b) shows an optical microscope photograph of the particles after polymerization. Figure 4 As shown in (b), it was confirmed that no hollow fine particles were obtained. Hereinafter, the obtained sample is referred to as "13FM solid".

[0357] [Example 4]

[0358] Except for changing the types and amounts of the components as shown in Table 1 below, polymerization was carried out in the same manner as in Example 1 to produce hollow fine particles containing a fluorine-containing resin.

[0359] Figure 5 (a) shows an optical microscope photograph of the suspended droplets before polymerization. Figure 5 (b) shows an optical microscope photograph of the particles after polymerization. Uniform suspended droplets were observed from the optical microscope photograph before polymerization. In addition, according to the optical microscope photograph after polymerization, a clear shell wall was confirmed in the system containing 10 mass % PS, suggesting that hollow particles containing fluorine-containing resin in the shell wall were produced.

[0360] Figure 6 (a) shows a SEM photograph of the obtained particles. Figure 6 (b) shows the EDX mapping of the shell wall. Figure 6 (c) shows an SEM photo of the crushed particles. It can be seen from the SEM photo that the produced particles are spherical and smooth particles. The elemental analysis of the shell wall was carried out by EDX mapping, and the results also confirmed that the shell wall contained fluorine. In addition, the particles were crushed and observed using SEM, and it was also confirmed that the inside of the particles was hollow. From these results, it can be seen that hollow particles containing fluorine-containing resin in the shell wall were produced in a system containing 10% by mass of PS. Hereinafter, this sample is recorded as "13FM1:1".

[0361] [Table 1]

[0362] Example 1 Comparative Example 1 Example 2 Example 3 Comparative Example 2 Example 4 Abbreviation 3FM1:1 3FM Solid 3FM1:2 5FM1:1 13FM solid 13FM1:1 EGDM(g) 0.33 0.33 0.22 0.33 0.33 0.33 3FM(g) 0.33 0.33 0.44 5FM(g) 0.33 13FM 0.33 0.33 PS(g) 0.066 0.066 0.066 0.066 Toluene(g) 0.594 0.594 0.594 0.590 0.660 V-70(mg) 26.7 26.7 26.7 26.7 26.7 26.7 PVA(mg) 20 20 20 20 20 20 Water(g) 20 20 20 20 20 20

[0363] [Example 5]

[0364] According to the composition of Table 2 below, a uniform oil phase was dispersed in an aqueous medium using a homogenizer to prepare suspension drops. The uniform oil phase was prepared by dissolving EGDM and 13FM in a toluene solution in which PS was dissolved at 25°C. After heating it to 70°C under a nitrogen atmosphere, BPO was added to the suspension and polymerized at 70°C at 400 rpm for 5 hours to prepare hollow fine particles containing fluororesin. It should be noted that in Table 2, BPO is benzoyl peroxide, which is a medium-temperature initiator.

[0365] [Table 2]

[0366] Example 5 EGDM(g) 0.33 3FM(g) 5FM(g) 13FM 0.44 PS(g) 0.077 Toluene(g) 0.770 BPO(mg) 26.7 PVA(mg) 20 Water(g) 20

[0367] Figure 7 (a) shows an optical microscope photograph before polymerization. Figure 8 (a) shows an optical microscope photograph after polymerization. Figure 8 (b) shows the SEM photo of the polymerized product. Figure 8 (a) It can be seen that a clear shell wall is formed. Figure 8 The SEM photograph of the crushed particles shown in (b) also confirmed that the interior of the particles was hollow, and the target hollow fine particles with a high fluorine content were successfully produced.

[0368] [evaluate]

[0369] The physical properties of the microparticles obtained in the examples and comparative examples were evaluated. As sampling and pretreatment conditions, the synthesized emulsion was allowed to stand fully, and an appropriate amount was carefully collected from the precipitated portion using a dropper. After air drying, it was dried using a blower dryer at 80°C for 24 hours. The sample was subjected to elemental analysis and thermal analysis (TG / DTA, DSC).

[0370] [Fluorine content]

[0371] 10 mg of the sample was burned by the oxygen bottle combustion method, and the decomposed gas was absorbed in 20 ml of deionized water. The fluoride ion concentration in the absorption liquid was measured by the fluorine selective electrode method (fluoride ion meter, Orion Co., Ltd., Model 901) to determine the mass % fluoride concentration.

[0372] Elemental analysis of fluorine was performed, and the composition (mass %) of the fluorine-containing monomer in the polymer was calculated from the analysis value (F mass %). Here, the amount of PS was uniformly calculated to be 10 mass % of the crosslinking agent. The results are shown in Table 3.

[0373] [Table 3]

[0374]

[0375] [Thermal decomposition temperature]

[0376] The temperature at which the mass reduction rate of the sample reached 1 mass % was measured using a differential thermal and thermogravimetric simultaneous measurement device (STA7200 manufactured by Hitachi High-Tech Science Corporation) under air atmosphere conditions and a temperature increase rate of 10°C / min. The results are summarized in Table 4.

[0377] [Table 4]

[0378]

[0379] [Glass transition temperature]

[0380] Using DSC (Differential Scanning Calorimeter: DSC7000 manufactured by Hitachi High-Tech Science Co., Ltd.), the temperature was increased (first round)-cooled-heated (second round) at 10°C / min in the temperature range of 30°C to 200°C, and the midpoint of the endothermic curve in the second round was taken as the glass transition temperature (°C). However, all samples were fully cross-linked, and therefore, as shown in Table 5, no clear glass transition temperature (Tg) and melting point (Tm) could be observed.

[0381] [Table 5]

[0382]

[0383] [Particle size]

[0384] The image analysis of the optical microscope photos of the hollow microparticles was calculated using the particle size analysis software LUZEX AP. Specifically, photos were taken at different positions, and the average particle size, maximum particle size, minimum particle size, and CV value were calculated in a manner such that the total number of particles was 50 or more. The results are shown in Table 6.

[0385] [Table 6]

[0386]

[0387] [Film Forming 1]

[0388] After blending the obtained hollow microparticle dispersion 3FM1:2 in an appropriate amount into the fluororesin dispersion SE-405 (solid content concentration 50%) manufactured by Daikin Industries, Ltd., it was mixed for 15 minutes using an ultrasonic cleaner. After that, a film was made on a PET substrate using a scraper adjusted to 15 mils, dried at room temperature, and then dried in a 60°C blower dryer for 12 hours. Various measurements were performed using the obtained film. Regarding the thickness, the PET substrate was measured together with the PET substrate using a micrometer, and then the value of the PET substrate alone was subtracted to obtain the film thickness. The film thickness was measured as an average of 5 points. In addition, the content of 3FM1:2 was calculated from the results of the fluorine element analysis.

[0389] In addition, a film using a 3FM solid core and a film formed only of SE-405 without adding fine particles were prepared in the same manner.

[0390] [Table 7]

[0391] particle Addition amount of microparticles Film thickness(μm) Membrane 1 Example 2 3FM1:2 5.60% by mass 125 Membrane 2 Example 2 3FM1:2 14.00% by mass 125 Membrane 3 Comparative Example 1 3FM Solid 2.80% by mass 109 Film 4 - none 0.00% by mass 100

[0392] [Cross-sectional SEM observation]

[0393] A cross-sectional SEM photograph of the film (microparticles: 3FM1:2, microparticle addition amount: 14.0 mass %) prepared as described above is shown in FIG. Fig. 9 and 10 The nested structure observed in the SEM observation of the individual particles was also observed in the cross-sectional SEM, and a hollow structure was also confirmed. The nested structure was confirmed in the particles with a large diameter, and the hollow structure was confirmed in the particles with a small diameter.

[0394] [Dielectric constant and dielectric loss tangent]

[0395] Aluminum was deposited on both sides of the film prepared above in vacuum to prepare a sample. For this sample, the electrostatic capacitance and dielectric loss tangent at a frequency of 1 kHz were measured at 25°C using an LCR meter. The relative dielectric constant was calculated from the obtained electrostatic capacitances as the dielectric constant. The results are shown in Table 8 below.

[0396] [Table 8]

[0397] particle Addition amount of microparticles Film thickness(μm) Relative dielectric constant Dielectric loss tangent Membrane 1 Example 2 3FM1:2 5.60% by mass 125 7.53±0.25 0.190 Membrane 2 Example 2 3FM1:2 14.00% by mass 125 7.41±0.50 0.172 Membrane 3 Comparative Example 1 3FM Solid 2.80% by mass 109 8.65±0.72 0.216 Film 4 - none 0.00% by mass 100 8.50±0.42 0.221

[0398] The results of dielectric loss tangent (tanδ) are summarized in the figure and shown in Fig.11 According to the composite rule, assuming that the tanδ of this system is linearly approximated, as shown in the figure, the results of the mixed solid particles are roughly on the theoretical curve, but the results of the hollow particles are obviously shifted downward, which is considered to be the effect of air (hollow).

[0399] [Film making 2]

[0400] Using 13FM1:1 as hollow fine particles, the films shown in Tables 9 and 10 below were prepared in the same manner as in the above-mentioned Film Preparation 1, and the film thickness, relative dielectric constant, and dielectric loss tangent of the films were measured. Compared with the film prepared from SE405 alone without using hollow fine particles, the relative dielectric constant and dielectric loss tangent of all the films were reduced.

[0401] [Table 9]

[0402]

[0403] [Table 10]

[0404]

Claims

1. A method for producing hollow particles, characterized in that: The process includes the following steps: a dispersing step of dispersing a solution containing a fluorinated monomer, a phase separation accelerator, and a non-polymerizable solvent in water to obtain a dispersion; and a polymerization step of polymerizing the fluorine-containing monomer to obtain hollow fine particles containing a fluorine-containing resin, The phase separation promoter is a polymer comprising polymerized units based on a monomer represented by the following general formula: CH2=CX 4 Y 2 Where, X 4 is H, CH3, F, Cl or CF3; Y 2 Cl, C6H4R 1 、C6H3R 2 R 3 、COOR 4 or OCOR 5 , where R 1 , R 2 , R 3 , R 4 and R 5 are independently H, OH, or an alkyl group having 1 to 40 carbon atoms which may be substituted with a halogen atom, The fluorine content of the fluorine-containing monomer is 30% by mass or more, The non-polymerizable solvent is an aromatic hydrocarbon, an ester, or a saturated hydrocarbon having 8 to 18 carbon atoms, or a halogen-substituted product thereof.

2. The method for producing hollow fine particles according to claim 1, wherein: The fluorine-containing monomer is the following general formula (B 1 ) shown in the monomer (B 1 ), CX 1 X 2 =CY 1 Z(B 1 ) Formula (B 1 ), X 1 , X 2 and Y 1 are independently H, CH3, F or Cl; Z is F, -Q-Rf 1 -A group represented by -Y, a group represented by the following formula, or -SO3H, [Chemistry 1] Where, X 6 ~X 10 are independently a hydrogen atom, a fluorine atom, or a hydrocarbon group having 1 to 8 carbon atoms which may be substituted by fluorine or chlorine; In-Q-Rf 1 In -Y, Q is a single bond, -O-, -O-(C=O)- or -C(=O)-O-, Rf 1 It is a fluorinated alkylene group having 1 to 20 carbon atoms which may contain ether bonds between carbon atoms, Y is F, H, -OH, -COOH, -COOR, and R in the -COOR is an alkyl group having 1 to 20 carbon atoms; Among them, X 1 , X 2 , Y 1 Any one of and Z contains one or more F.

3. The method for producing hollow fine particles according to claim 1, wherein: The fluorine-containing monomer is the following general formula (C 1 ) shown in the fluorinated acrylic monomer (C 1 ), CH2=CX 3 -COORf 2 (C 1 ) Where, X 3 is H, CH3, F, Cl or CF3; Rf 2 It is a fluorine-containing alkyl group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms.

4. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The phase separation promoter is dissolved in the non-polymerizable solvent at room temperature, and The Sp value of the phase separation promoter is SA (J / cm 3 ) 1 / 2 , the Sp value of the non-polymerizable solvent is set to SB (J / cm 3 ) 1 / 2 When , the following relationship is satisfied: │SA-SB│<3(J / cm 3 ) 1 / 2 .

5. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The phase separation promoter is at least one selected from the group consisting of aromatic vinyl polymers and polyalkyl (meth)acrylates.

6. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The solution further comprises a cross-linking monomer.

7. The method for producing hollow fine particles according to claim 6, wherein: In the fluorine-containing resin, the polymerized units based on the crosslinkable monomer account for 30 to 70% by mass of the total polymerized units, and the polymerized units based on the non-fluorine-containing monomer account for 0 to 50% by mass of the total polymerized units.

8. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The dispersion process is the following process: A step of dispersing the solution in water at a temperature of 50° C. or higher to obtain a dispersion; or A step of dispersing the solution in water at a temperature lower than 50° C. to obtain a dispersion, and heating the obtained dispersion to a temperature of 50° C. or higher.

9. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: After the dispersing step and before the polymerization step, the method further includes adding an oil-soluble initiator to the dispersion.

10. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The method comprises the step of removing the non-polymerizable solvent from the hollow fine particles obtained in the polymerization step.

11. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The average particle size of the hollow fine particles is 1.0 μm or more.

12. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The fluorine-containing monomer is the following general formula (C 1 ) shown in the fluorinated acrylic monomer (C 1 ), CH2=CX 3 -COORf 2 (C 1 ) Where, X 3 CH3, Rf 2 It is a fluorine-containing alkyl group having 2 to 6 carbon atoms which may contain an ether bond between carbon atoms.

13. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The phase separation promoter is polystyrene, The non-polymerizable solvent is toluene.

14. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: In the solution, the content of the monomer is 0.8 to 3.5 parts by mass, and the content of the phase separation promoter is 0.05 to 0.2 parts by mass, relative to 1 part by mass of the non-polymerizable solvent. The non-polymerizable solvent is used in an amount of 0.5 to 5 parts by mass relative to 1 part by mass of the monomer. In the hollow fine particles, the content of the phase separation promoter is 5% by mass to 20% by mass based on the fluorine-containing resin.

15. The method for producing hollow fine particles according to any one of claims 1 to 3, wherein: The average particle size of the hollow particles is 5.0 μm to 30.0 μm.

16. The method for producing hollow fine particles according to claim 1, wherein: The fluorine-containing resin comprises a fluorine-containing acrylic monomer (C 2 ) and a polymer based on at least one crosslinkable monomer (E) selected from the group consisting of di(meth)acrylates, tri(meth)acrylates and divinyl compounds, Based on the fluorinated acrylic monomer (C 2 ) of the polymerized unit (C 2 ) and the mass ratio of the polymerized units based on the crosslinkable monomer (E), that is, the fluorinated acrylic monomer (C 2 ) / crosslinking monomer (E) is 60 / 40 to 40 / 60, The fluorinated acrylic monomer (C 2 ) is represented by the following general formula (C 2 ), CH2=CX 3 -COORf 2 (C 2 ) Where, X 3 is H, CH3, F, Cl or CF3; Rf 2 It is a fluorine-containing alkyl group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms.

17. A hollow particle, characterized in that: It contains: a fluorine-containing resin D containing polymerized units based on a fluorine-containing monomer and a phase separation accelerator, wherein the average particle size of the hollow fine particles is 1.0 μm or more, The phase separation promoter is a polymer comprising polymerized units based on a monomer represented by the following general formula: CH2=CX 4 Y 2 Where, X 4 is H, CH3, F, Cl or CF3; Y 2 Cl, C6H4R 1 、C6H3R 2 R 3 、COOR 4 or OCOR 5 , where R 1 , R 2 , R 3 , R 4 and R 5 are independently H, OH, or an alkyl group having 1 to 40 carbon atoms which may be substituted with a halogen atom, The fluorine content of the fluorine-containing resin D is 15% by mass or more.

18. The hollow fine particles according to claim 17, wherein The fluorine-containing monomer is the following general formula (B 2 ) shown in the monomer (B 2 ), CX 1 X 2 =CY 1 Z(B 2 ) Formula (B 2 ), X 1 , X 2 and Y 1 are independently the same or different and are H, CH3, F or Cl; Z is F, -Q-Rf 1 -A group represented by -Y, a group represented by the following formula, or -SO3H, [Chemistry 2] Where, X 6 ~X 10 are independently a hydrogen atom, a fluorine atom, or a hydrocarbon group having 1 to 8 carbon atoms which may be substituted by fluorine or chlorine; In-Q-Rf 1 In -Y, Q is a single bond, -O-, -O-(C=O)- or -C(=O)-O-, Rf 1 It is a fluorinated alkylene group having 1 to 20 carbon atoms which may contain ether bonds between carbon atoms, Y is F, H, -OH, -COOH, -COOR, and R in the -COOR is an alkyl group having 1 to 20 carbon atoms; Among them, X 1 , X 2 , Y 1 Any one of and Z contains one or more F.

19. The hollow fine particles according to claim 17, wherein The fluorine-containing monomer is the following general formula (C 2 ) shown in the fluorinated acrylic monomer (C 2 ), CH2=CX 3 -COORf 2 (C 2 ) Where, X 3 is H, CH3, F, Cl or CF3; Rf 2 It is a fluorine-containing alkyl group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms.

20. The hollow fine particles according to any one of claims 17 to 19, wherein The phase separation promoter is at least one selected from the group consisting of aromatic vinyl polymers and polyalkyl (meth)acrylates.

21. The hollow fine particles according to any one of claims 17 to 19, wherein The fluorine-containing resin D further includes a polymerized unit based on a crosslinkable monomer.

22. The hollow fine particles according to claim 21, wherein In the fluorine-containing resin D, the polymerized units based on the crosslinkable monomer account for 30 to 70% by mass of the total polymerized units, and the polymerized units based on the non-fluorine-containing monomer account for 0 to 50% by mass of the total polymerized units.

23. The hollow fine particles according to any one of claims 17 to 19, wherein The hollow fine particles are composed of a shell composed of the fluorine-containing resin D and a hollow portion, and have a single-hole structure.

24. The hollow fine particles according to any one of claims 17 to 19, wherein The fluorine-containing monomer is the following general formula (C 1 ) shown in the fluorinated acrylic monomer (C 1 ), CH2=CX 3 -COORf 2 (C 1 ) Where, X 3 CH3, Rf 2 It is a fluorine-containing alkyl group having 2 to 6 carbon atoms which may contain an ether bond between carbon atoms.

25. The hollow fine particles according to any one of claims 17 to 19, wherein The phase separation promoter is polystyrene.

26. The hollow fine particles according to any one of claims 17 to 19, wherein The content of the phase separation accelerator relative to the fluorine-containing resin D is 5% by mass to 20% by mass.

27. The hollow fine particles according to any one of claims 17 to 19, wherein The average particle size of the hollow particles is 5.0 μm to 30.0 μm.

28. The hollow fine particles according to claim 17, wherein The fluorine-containing resin D comprises a fluorine-containing acrylic monomer (C 2 ) and a polymer based on at least one crosslinking monomer (E) selected from the group consisting of di(meth)acrylates, tri(meth)acrylates and divinyl compounds, Based on the fluorinated acrylic monomer (C 2 ) of the polymerized unit (C 2 ) and the mass ratio of the polymerized units based on the crosslinkable monomer (E), that is, the fluorinated acrylic monomer (C 2 ) / crosslinking monomer (E) is 60 / 40 to 40 / 60, The fluorinated acrylic monomer (C 2 ) is represented by the following general formula (C 2 ), CH2=CX 3 -COORf 2 (C 2 ) Where, X 3 is H, CH3, F, Cl or CF3; Rf 2 It is a fluorine-containing alkyl group having 1 to 20 carbon atoms which may contain an ether bond between carbon atoms.

29. The hollow fine particles according to any one of claims 17 to 19, which are hollow fine particles for electronic materials. 30 . A curable composition comprising the hollow fine particles according to claim 17 . 31 . A coating composition comprising the hollow fine particles according to claim 17 .

Citation Information

Patent Citations

  • Battery pack and power system

    CN211350890U

  • JP1973040414B1

  • Method for manufacturing fine particles containing objective component, fine hollow polymer particles, and manufacturing method therefor

    JP2003096108A

  • Hollow resin microparticle and antireflective film

    JP2005213366A

  • Hollow resin particle

    JP2008231241A